2022
DOI: 10.1302/0301-620x.104b4.bjj-2021-1708.r1
|View full text |Cite
|
Sign up to set email alerts
|

The British Orthopaedic Surgery Surveillance study: Perthes’ disease

Abstract: Aims The aim of this study was to evaluate the epidemiology and treatment of Perthes’ disease of the hip. Methods This was an anonymized comprehensive cohort study of Perthes’ disease, with a nested consented cohort. A total of 143 of 144 hospitals treating children’s hip disease in the UK participated over an 18-month period. Cases were cross-checked using a secondary independent reporting network of trainee surgeons to minimize those missing. Clinician-reported outcomes were collected until two years. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Despite existing evidence highlighting which patients may benefit from surgery instead of conservative treatment, there are several surgical approaches within the literature, and most have positive reported outcomes. [18][19][20] Perry et al 32 conducted an anonymized comprehensive cohort study of Perthes' disease across 143 hospitals in the UK and reported considerable variation in how these patients were treated. In their study, despite a high proportion (36.4%) of patients undergoing surgical containment, the authors report no evidence of improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite existing evidence highlighting which patients may benefit from surgery instead of conservative treatment, there are several surgical approaches within the literature, and most have positive reported outcomes. [18][19][20] Perry et al 32 conducted an anonymized comprehensive cohort study of Perthes' disease across 143 hospitals in the UK and reported considerable variation in how these patients were treated. In their study, despite a high proportion (36.4%) of patients undergoing surgical containment, the authors report no evidence of improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…and physician specialty at the time of the initial presentation. As severity is thought to be a consequence of delay, the slip severity classification and Southwick angle measurement were not included as covariates in the models 4,5,9 . SCFE severity was assessed on anteroposterior and lateral radiographs by 2 authors (L.M.S.…”
Section: Methodsmentioning
confidence: 99%
“…increases the risks of osteonecrosis, chondrolysis, and advanced hip arthritis [9][10][11][12][13][14] .…”
mentioning
confidence: 99%
“…176 Clinical trials are currently underway and their results awaited. 177 The recent study that casts doubt on the effectiveness of containment surgery 170 clearly emphasizes the urgent need to embark on well-designed, prospective studies with adequate follow-up (ideally randomized controlled trials (RCTs)) to clarify the role of the current approach to treatment of LCPD. Realizing the need for robust prospective studies, the International Perthes Study Group (IPSG) has begun collecting data prospectively and undertaking studies on various aspects of LCPD.…”
Section: Future Directionsmentioning
confidence: 99%